Sydney Tomlinson: capstone - Tomlinson, Sydney, artist (Colorado State University. Libraries, 2024)
The artist's statement: As a graphic designer, I employ a variety of artistic mediums and techniques to create distinctive and visually engaging designs. My designs are a reflection of the complexities inherent in the human experience. From exploring psychological themes to addressing societal issues, my creative process delves into the intricate interplay between language and imagery. Through this fusion, I aim to create works that resonate deeply with viewers, provoking thought and transcending conventional boundaries.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design